Needs for Reproductive Health Education for Deaf Students in Singaraja District, Bali Province - Nyoman Sri Ariantini; Desak Putu Yuli Kurniati; Dyah Pradnyaparamita Duarsa (Universitas Triatma Mulya, 2019)
Introduction. Adolescents with hearing impairment face a number of exclusion due to their limitation, including lack of access to information on reproductive health. This study was aimed to explore needs for sexual and reproductive health education for students with hearing impairment at SLB B Negeri Singaraja. Methods. A qualitative study was conducted at Singaraja District. Data were collected at through in-depth interviews to 19 informants. Informants were purposively selected based on their specific roles. Our informants included ten students with hearing impairment, one head of school, five teachers, and three parents or carers. Data were analysed using a thematic approach. Results. The majority of students with hearing impairment were having low level of knowledge associated to sexual and reproductive health. However, sexual and reproductive health practices between adolescents with and without hearing impairment were generally comparable. Needs for sexual and reproductive health education must cover several elements: (1) education material must be tailored based on age, (2) learning methods should be tailored based on their intellectual ability, and (3) learning methods must use contextual and real model approach to allow better transfer of information. Teachers faced difficulty to provide sexual and reproductive health education for students with hearing impairment even though some modules are already available. Conclusion. Students with hearing impairment at SLB B Singaraja State need more simple learning pictures and videos that are accompanied by written texts and sign language movements so that it is easier to understand the material delivered by the teacher, where the reproductive health education material needed is age-appropriate material and the development of each individual, while the reproductive health learning methods needed by deaf students are simpler learning methods while still using sign language.